Fatalism, medical mistrust, and pretreatment health‐related quality of life in ethnically diverse prostate cancer patients. Issue 3 (9th November 2015) - Bustillo, Natalie Escobio; McGinty, Heather L.; Dahn, Jason R.; Yanez, Betina; Antoni, Michael H.; Kava, Bruce R.; Penedo, Frank J.
Abstract: Objective: Few studies have examined the impact of cultural processes prevalent in minority ethnic groups such as cancer fatalism and medical mistrust on health‐related quality of life (HRQoL) following a cancer diagnosis. The present study examined relationships among ethnicity, HRQoL, and two possible cultural vulnerability factors—fatalistic attitudes and medical mistrust—among an ethnically diverse sample of men with prostate cancer (PC) prior to undergoing active treatment. Methods: A total of 268 men with localized PC (30% African American, 29% Hispanic, and 41% non‐Hispanic White) were assessed cross‐sectionally prior to active treatment. Path analyses examined relationships among ethnicity, vulnerability factors, and HRQoL. Results: Ethnicity was not related to HRQoL after controlling for relevant covariates. Hispanic men reported greater cancer fatalism compared with non‐Hispanic White men ( β  = 0.15, p  = 0.03), and both Hispanics ( β  = 0.19, p  < 0.01) and African Americans ( β  = 0.20, p  < 0.01) reported greater medical mistrust than non‐Hispanic Whites. Fatalism demonstrated a trend toward negatively impacting physical well‐being ( β  = −0.12, p  = 0.06), but was not significantly related to emotional well‐being ( β  = −0.10, p  = 0.11). Greater medical mistrust was associated with poorer physical ( β  = −0.14, p  = 0.03) and emotional well‐being ( β  = −0.13, p  = 0.04). Conclusions: Results indicate that fatalistic attitudes and medical system mistrust were more prevalent among minority men. Less trust in the medical system was associated with poorer physical and emotional well‐being. Attention to perceptions of the healthcare system and its relation to HRQoL may have implications for targeting culturally driven attitudes that may compromise adjustment to a PC diagnosis.Copyright © 2015 John Wiley & Sons, Ltd.